2021
DOI: 10.33963/kp.15919
|View full text |Cite
|
Sign up to set email alerts
|

Use of T-wave duration and Tpeak-Tend interval as new prognostic markers for patients treated with cardiac resynchronization therapy

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives 4.0 International License (CC BY-NC-ND 4.0), allowing third parties to download articles and share them with others, provided the original work is properly cited, not changed in any way, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Usalp et al investigated the length of Tp-e and T wave in cardiac resynchronization therapy. They found that a reduction in the duration of these markers was a significant predictor of a favorable response to the treatment [ 87 ]. Moreover, Banavalikar et al found that Tp-e predicts ventricular tachyarrhythmias in heart failure patients after cardiac resynchronization therapy [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Usalp et al investigated the length of Tp-e and T wave in cardiac resynchronization therapy. They found that a reduction in the duration of these markers was a significant predictor of a favorable response to the treatment [ 87 ]. Moreover, Banavalikar et al found that Tp-e predicts ventricular tachyarrhythmias in heart failure patients after cardiac resynchronization therapy [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…The measurements were performed on lead II and lead V5, and the longest QT and Tp‐e intervals were used for the analyses. 17 , 18 Then, Tp‐e was divided by the QTc time to calculate the ratio of Tp‐e / QTc.…”
Section: Methodsmentioning
confidence: 99%
“…The Tp–e interval is defined as the interval from the peak of the T wave to the end of the T wave. The measurements were performed on lead II and lead V5, and the longest QT and Tp‐e intervals were used for the analyses 17,18 . Then, Tp‐e was divided by the QTc time to calculate the ratio of Tp‐e / QTc.…”
Section: Methodsmentioning
confidence: 99%